Squaric acid derivative compound, preparation method thereof and application of squaric acid derivative compound in battery
By developing a new type of quaternary acid derivative compound as an electrolyte additive, the problems of low conductivity and ion mobility of lithium quaternary acid are solved, and the high-temperature storage and high-temperature circulation performance of lithium-ion batteries are significantly improved, and higher energy is achieved. Density and cycle life.
Patent Information
- Application Number
- CN202411571404.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In the prior art, the conductivity and ion mobility of lithium quaternate are low, resulting in an increase in the internal resistance of the positive electrode sheet, affecting the performance of the electrode material, and the electrochemical activity is poor, so the lithium/sodium supplement effect cannot be fully utilized, which limits the Application in positive electrode lithium supplement technology.
A new type of cube acid-derived compound and its preparation method are provided. This compound can be used as a functional additive in the electrolyte, inhibit the dissolution of metal ions in the positive electrode material, improve the high-temperature storage and high-temperature circulation performance of the battery, and is used as a lithium salt to Lithium supplementation.
By inhibiting the dissolution of metal ions in the positive electrode material, a stable SEI film is formed, which significantly improves the high-temperature storage and high-temperature cycling performance of the battery, and enhances the energy density and cycle life of the battery.
Smart Images

Figure CN119431303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material synthesis, and in particular to a compound used in a battery, and more particularly to a square acid derivative compound and a preparation method thereof, and application of the compound in a battery. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, portable electronic products, drones, distributed energy storage, and smart grids, higher requirements have been put forward for various battery performances, among which the requirement for improving the energy density of batteries is particularly urgent. To improve the energy density of batteries, the following methods are currently used. (1) Use positive electrode materials with higher energy density, such as high-nickel ternary positive electrode materials (NCM, NCA). (2) Use high-capacity silicon and tin-based alloys as negative electrode active materials. (3) Optimize the battery structure to improve the energy density of the battery, such as blade battery technology. (4) Use battery lithium supplementation technology to improve the energy density of the battery. During the formation process of lithium-ion batteries, a layer of nanostructured SEI film will be formed on the surface of the negative electrode, which will consume part of the active lithium and cause the loss of battery capacity. The irreversible capacity loss of the most widely used graphite negative electrode is 6%, while the irreversible capacity loss of high-specific-capacity silicon-based and tin-based alloy negative electrodes is as high as 10-20%. Therefore, lithium supplementation technology can effectively improve the initial efficiency of the battery, improve the energy density of the battery and extend the cycle life.
[0003] Lithium replenishment technology can be divided into positive electrode replenishment and negative electrode replenishment. Among them, negative electrode replenishment technology has been studied earlier, including physical mixing of metallic lithium, chemical replenishment, electrochemical replenishment, etc. However, due to the activity of metallic lithium materials, its process difficulty is very high and has not yet been widely used. In recent years, positive electrode replenishment technology has received widespread attention and research. Positive electrode replenishment technology is to add lithium replenishment materials to the positive electrode materials of lithium batteries. Positive electrode replenishment materials have the advantages of stable chemical properties and easy synthesis. Moreover, positive electrode replenishment materials can be directly added during the homogenization process of positive electrode slurry. The preparation process is simple and the cost is low. It is currently the most promising lithium replenishment technology. At present, the industry has adopted lithium squarate as a positive electrode replenishment additive, which can be used as a sacrificial lithium salt to replenish the irreversible capacity loss of lithium ions, thereby improving the cycle performance of lithium-ion batteries. At present, the application of squaric acid in batteries is mainly to neutralize it with alkali metal compounds to directly convert it into lithium salt or sodium salt for use as a lithium / sodium supplement additive for positive electrode materials. However, the conductivity and ion mobility of lithium squaric acid are very low, which leads to an increase in the internal resistance of the positive electrode plate, affecting the performance of the electrode material. In addition, the electrochemical activity is poor and the lithium / sodium supplement effect cannot be fully exerted, thus limiting its application in positive electrode lithium supplement technology. Summary of the invention
[0004] Based on the above problems, the purpose of the present invention is to provide a novel square acid derivative compound and a preparation method thereof. The square acid derivative compound can be directly used in the electrolyte as a functional additive, which can inhibit the dissolution of metal ions in the positive electrode material and cause the oxidative decomposition of the electrolyte, thereby improving the high-temperature storage and high-temperature cycle performance of the battery. The lithium salt of this novel square acid derivative compound can also be used as an electrolyte salt, thereby playing a role in lithium supplementation.
[0005] To achieve the above object, the present invention provides a squaric acid derivative compound in the first aspect, the structural formula of which is shown in Formula 1, Formula 2, Formula 3 or Formula 4, wherein X is selected from SO 2 , SO, CO, BR, PR, PO-R or Si-R 2 ,Y is selected from BR 2 , PR 2 , PO-R 2 or PR 4 , Z is selected from SO, C or PR, W is selected from B, P or PR 2 , R is hydrogen, halogen or C 1 ~C 3 of alkyl.
[0006]
[0007] The left side of the square acid derivative compound of the present invention has high stability and conjugated structure, and can be complexed with positive electrode metal ions to stabilize the structure. On the other hand, the right side structure of the square acid derivative compound can introduce heteroatoms to form bonds such as S=O, C=O, PR, BR, Si-R, etc., which can increase the solubility of the square acid derivative compound in the electrolyte, and at the same time, a stable SEI film can be formed during the battery cycle process, which can inhibit the dissolution of metal ions in the positive electrode material and cause the oxidative decomposition of the electrolyte. Therefore, after adding the square acid derivative compound to the non-aqueous electrolyte of the secondary battery, the high temperature storage and high temperature cycle performance of the secondary battery under high voltage can be improved.
[0008] As a technical solution of the present invention, the square acid derivative compound includes at least one of compound 1 to compound 8.
[0009]
[0010] The second aspect of the present invention provides a method for preparing a squaric acid derivative compound, comprising the steps of:
[0011] (1) mixing squaric acid and a solvent to form a first solution;
[0012] (2) adding an electrophilic reagent to the first solution to carry out a substitution reaction, or first adding a salt to the first solution and then adding the electrophilic reagent to carry out a substitution reaction, wherein the electrophilic reagent is a silicon halide, a phosphorus halide, a boron halide, a sulfur halide or an ester compound, and the salt is a lithium salt or a sodium salt;
[0013] (3) Purification and drying after the reaction.
[0014] The preparation method of the present invention is simple, and a square acid derivative compound as described in Formula 1 or Formula 3 can be obtained by performing a substitution reaction with square acid and electrophilic reagents such as silicon halides, phosphorus halides, boron halides, sulfur halides, ester compounds, etc. Square acid derivative compounds as described in Formula 2 or Formula 4 can be obtained by performing a substitution reaction with square acid and electrophilic reagents such as silicon halides, phosphorus halides, boron halides, sulfur halides, ester compounds, etc. under the action of salt. The obtained square acid derivative compound can improve the high temperature storage and high temperature cycle performance of the battery.
[0015] As a technical solution of the present invention, the solvent includes at least one of a halogenated hydrocarbon solvent, an aliphatic hydrocarbon, an ether solvent, a ketone solvent, an ester solvent and a nitrile solvent.
[0016] As a technical solution of the present invention, the reaction temperature of the substitution reaction is -20 to 90°C.
[0017] As a technical solution of the present invention, the molar ratio of the squaric acid to the electrophilic reagent is 1:0.5-2.1.
[0018] As a technical solution of the present invention, an oxidation step is also included between step (2) and step (3), and the product of the substitution reaction is oxidized.
[0019] As a technical solution of the present invention, the electrophilic reagent is selected from at least one of silicon tetrachloride, trimethylsilyl chloride, dimethylsilyl chloride, monomethylsilyl chloride, thionyl chloride, phosphorus trichloride, phosphorus pentachloride, phosphorus tribromide, phosphorus pentabromide, boron trichloride, boron trifluoride, boron trifluoride ether complex, dimethyl carbonate complex, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and the salt is selected from lithium hexafluorophosphate, lithium tetrafluoroborate, sodium hexafluorophosphate or sodium tetrafluoroborate.
[0020] The third aspect of the present invention provides the use of a squaric acid derivative compound in a secondary battery.
[0021] The fourth aspect of the present invention provides an electrolyte solution, comprising a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises the aforementioned squaric acid derivative compound, and the squaric acid derivative compound accounts for 0.01 to 2.00% of the mass of the electrolyte solution.
[0022] As a technical solution of the present invention, the electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorophosphate and lithium difluorobis(oxalato)phosphate, and the non-aqueous organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, butyl acetate, γ-butyrolactone, propyl propionate, butyl propionate and ethyl butyrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the mass spectrum of compound 5 in Example 4.
[0024] Figure 2 This is the mass spectrum of compound VI in Example 5.
[0025] Figure 3 This is the mass spectrum of compound VII in Example 6. DETAILED DESCRIPTION
[0026] The squaric acid derivative compound of the present invention can be used in material synthesis and secondary batteries. In particular, the squaric acid derivative compound is used in secondary batteries such as lithium ion batteries or sodium ion batteries, and the squaric acid derivative compound can be used as an electrolyte additive to improve the high temperature storage and high temperature cycle performance of the secondary battery.
[0027] Secondary batteries include positive electrode active materials, negative electrode active materials and electrolytes. If used in lithium-ion batteries, the positive electrode active materials may be layered transition metal lithium oxides. The layered transition metal lithium oxides may be, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ) and coatings and dopants of lithium cobalt oxide. If the secondary battery is a sodium ion battery, the positive electrode active material may be a layered transition metal sodium oxide. The layered transition metal sodium oxide may be, but is not limited to, sodium cobalt oxide (such as NaCoO 2 ) and sodium cobalt oxide coatings and dopants. The negative electrode active material includes at least one of a carbon-based material, a silicon-based material, lithium titanate, and a tin-based material. Among them, the carbon-based material may be, but is not limited to, at least one of artificial graphite, natural graphite, hard carbon, soft carbon, graphene, and mesophase carbon microspheres. The silicon-based material may be, but is not limited to, at least one of a silicon element, a silicon-oxygen composite material, a silicon-carbon composite material, and a silicon alloy material. The tin-based material may include a tin element, a tin-carbon composite material, a tin-oxygen composite material, and a tin alloy compound.
[0028] The electrolyte solution includes an electrolyte salt, a nonaqueous organic solvent, and additives.
[0029] The electrolyte salt may be, but is not limited to, at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, and lithium difluorobisoxalatophosphate.
[0030] The non-aqueous organic solvent is selected from carbonate and / or carboxylic acid ester. Further, the non-aqueous organic solvent is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (PC), propylene carbonate (PC), butyl acetate, γ-butyrolactone, propyl propionate, butyl propionate and ethyl butyrate.
[0031] The additive is a square acid derivative compound, and further, the additive is a square acid derivative compound with a structural formula as shown in Formula 1, Formula 2, Formula 3 or Formula 4. X is selected from SO 2 , SO, CO, BR, PR, PO-R or Si-R 2 ,Y is selected from BR 2 , PR 2 , PO-R 2 or PR 4 , Z is selected from SO, C or PR, W is selected from B, P or PR 2 , R is hydrogen, halogen or C 1 ~C 3 of alkyl.
[0032]
[0034] Furthermore, the square acid derivative compound includes at least one of Compound 1 to Compound 8.
[0035]
[0036] The square acid derivative compound accounts for 0.01-2.00% of the mass of the electrolyte. As an example, the proportion of the square acid derivative compound can be but is not limited to 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.30%, 0.50%, 0.80%, 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, and 2.00%.
[0037] The preparation method of a square acid derivative compound comprises the following steps.
[0038] (1) Squaric acid and a solvent are mixed to form a first solution.
[0039] (2) adding an electrophilic reagent to the first solution to carry out a substitution reaction or first adding a salt to the first solution and then adding the electrophilic reagent to carry out a substitution reaction.
[0040] (3) Purification and drying after the reaction.
[0041] Wherein, the solvent in step (1) includes at least one of a halogenated hydrocarbon solvent, an aliphatic hydrocarbon, an ether solvent, a ketone solvent, an ester solvent and a nitrile solvent. Further, the halogenated hydrocarbon solvent may be dichloromethane, chloroform, 1,2-dichloroethane or tetrachloroethane, the aliphatic hydrocarbon solvent may be n-hexane or cyclohexane, the ether solvent may be ether, methyl tert-butyl ether, ethylene glycol dimethyl ether, tetrahydrofuran or dioxane, the ketone solvent may be acetone, cyclohexanone or 4-methyl-2-pentanone, the ester solvent may be dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate or propyl acetate, and the nitrile solvent may be acetonitrile. The square acid and the solvent are mixed evenly to form a clear and transparent solution or suspension.
[0042] In step (2), the electrophilic reagent is a silicon halide, a phosphorus halide, a boron halide, a sulfur halide or an ester compound. Further, the electrophilic reagent is selected from at least one of silicon tetrachloride, trimethylsilyl chloride, dimethylsilyl chloride, monomethylsilyl chloride, thionyl chloride, phosphorus trichloride, phosphorus pentachloride, phosphorus tribromide, phosphorus pentabromide, boron trichloride, boron trifluoride, boron trifluoride ether complex, dimethyl carbonate complex, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. The salt is a lithium salt or a sodium salt, and further, the salt is selected from lithium hexafluorophosphate, lithium tetrafluoroborate, sodium hexafluorophosphate or sodium tetrafluoroborate. The square acid derivative compound described in Formula 1 or Formula 3 can be obtained by performing a substitution reaction using square acid and an electrophilic reagent. By using a square acid and an electrophilic reagent to carry out a substitution reaction under the action of a salt, a square acid derivative compound as described in Formula 2 or Formula 4 can be obtained. The square acid derivative compound as described in Formula 2 or Formula 4 is a salt, which can not only be used as an additive to improve the performance of the battery, but also can replace part of the lithium salt to serve as an electrolyte component.
[0043] The reaction temperature of the substitution reaction is -20 to 90°C. As an example, the reaction temperature can be, but is not limited to, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, and 90°C. The time of the substitution reaction is 2 to 24h. As an example, the reaction time can be, but is not limited to, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, and 24h. The molar ratio of the square acid to the electrophilic reagent is 1:0.5 to 2.1. As an example, the molar ratio of the two can be, but is not limited to, 1:0.5, 1:0.7, 1:1.0, 1:1.2, 1:1.5, 1:1.8, 1:2.0, and 1:2.1. In order to obtain a highly oxidizable substance, a square acid derivative compound, an oxidation step may be further included between step (2) and step (3) to oxidize the product of the substitution reaction. For example, to obtain compound 1, a square acid-cyclic sulfite compound may be prepared first, and then sodium hypochlorite or ozone may be used for oxidation to obtain a square acid-cyclic sulfate compound. For example, after synthesizing compound 3, sodium hypochlorite or ozone may be used for oxidation to obtain compound 4.
[0044] In step (3), the purification method is washing, filtering or recrystallization. Among them, washing can be carried out by aqueous hydrochloric acid solution, saturated brine or water and multiple washing. Filtration can be carried out by centrifugal stratification, vacuum filtration or ordinary filtration. Recrystallization can use a mixed solvent of ethanol / water, and drying can be carried out in an oven for vacuum drying. The temperature of vacuum drying can be 40 to 120°C. As an example, the temperature can be but is not limited to 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C.
[0045] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0046] Part I: Preparation of Squaric Acid Derivatives
[0047] Example 1
[0048] This embodiment is for preparing compound 1, and its synthesis reaction formula is as follows. The preparation method includes the following steps.
[0049]
[0050] (1) In a 500 ml three-necked flask, add 11.4 g of squaric acid and 88 g of anhydrous acetonitrile and stir to mix uniformly to form a first solution.
[0051] (2) Then slowly drop 12.5 g of thionyl chloride and carry out substitution reaction at 35° C. for 7.5 h to obtain a pre-solution of squaric acid-cyclic sulfite, and then concentrate the pre-solution, cool and crystallize to obtain 14.4 g of crude squaric acid-cyclic sulfite. Then put the obtained crude squaric acid-cyclic sulfite into a new three-necked flask, add 80 g of acetonitrile and 14 g of sodium bicarbonate aqueous solution, control the temperature at -20° C., drop 67 g of sodium hypochlorite aqueous solution to carry out oxidation reaction to obtain an acetonitrile solution containing squaric acid-cyclic sulfate compound.
[0052] (3) After concentration, crystallization and vacuum drying at 50°C, 13.8 g of compound 1 was obtained with a yield of 87%.
[0053] Example 2
[0054] This embodiment is for preparing compound 2, and its synthesis reaction formula is as follows, and its preparation method includes the following steps.
[0055]
[0056] (1) In a 500 ml three-necked flask, add 11.4 g of squaric acid and 34.2 g of methanol and stir to form a first solution.
[0057] (2) Then, 45.6 g of dimethyl carbonate and 0.02 g of potassium carbonate were slowly added and refluxed at 75° C. for 12 h to carry out the substitution reaction until the solution became clear.
[0058] (3) After concentration, crystallization, filtration and vacuum drying at 80°C, 12.3 g of compound 2 was obtained with a yield of 88%.
[0059] Example 3
[0060] This embodiment is for preparing compound 3 and compound 4. The reaction formula is as follows, and the preparation method includes the following steps.
[0061]
[0062] (1) In a 500 ml three-necked flask, add 11.4 g of squaric acid and 89 g of anhydrous acetonitrile and stir to mix uniformly to form a first solution.
[0063] (2) Then slowly add 13.7g of phosphorus trichloride dropwise at 35°C to carry out substitution reaction for 7.0h. During the reaction, the acid generated by the reaction is absorbed by sodium hydroxide. After the reaction, the mother liquor is concentrated and filtered, and dried at 60°C to obtain 16g of a squaric acid-cyclic chlorophosphite compound. The obtained 16g of squaric acid-cyclic chlorophosphite compound is continuously put into a new anhydrous reaction container, and then 80g of anhydrous acetonitrile and 10.4g of anhydrous potassium fluoride are added to reflux reaction at 80°C for 24h. After the reaction, the mother liquor is filtered, concentrated, filtered, washed, and vacuum dried at 60°C to obtain 13.1g of compound III, with a yield of 90%.
[0064] The obtained 13.1 g of compound 3 was added to a new anhydrous reaction container, and then 72 g of toluene was added. The reaction temperature was set to 40°C, and then oxygen was introduced into the container for reaction. The progress of the reaction was monitored by LCMS until the raw material peak disappeared, and then the oxygen was stopped. The mother liquor was then concentrated, crystallized, and vacuum dried at 50°C to obtain 12.4 g of compound 4 with a yield of 86%.
[0065] Example 4
[0066] This embodiment is for preparing compound 5, the reaction formula is as follows, and its preparation method includes the following steps.
[0067]
[0068] (1) In a 500 ml three-necked flask, 11.4 g of squaric acid, 15.1 g of lithium hexafluorophosphate, and 113 g of ethyl methyl carbonate were added and stirred to form a first solution.
[0069] (2) Then, 8.5 g of silicon tetrachloride was slowly added dropwise and the substitution reaction was carried out at 35° C. for 5.5 h.
[0070] (3) The reaction solution was vacuumed to remove acid, concentrated, crystallized, filtered, and vacuum dried at 60°C to obtain 21.5 g of compound 5 with a yield of 95%. The mass spectrum of the obtained compound 5 is shown in Figure 1 As shown, it can be seen from the mass spectrum that compound 5 can be synthesized.
[0071] Example 5
[0072] This embodiment is for preparing compound 6, the reaction formula is as follows, and its preparation method includes the following steps.
[0073]
[0074] (1) In a 500 ml three-necked flask, 22.8 g of squaric acid, 15.1 g of lithium hexafluorophosphate, and 113 g of ethyl methyl carbonate were added and stirred to form a first solution.
[0075] (2) Then, 17.0 g of silicon tetrachloride was slowly added dropwise and the substitution reaction was carried out at 35° C. for 7.5 h.
[0076] (3) The reaction solution was vacuumed to remove acid, concentrated, crystallized, filtered, and vacuum dried at 60°C to obtain 28.2 g of compound 6 with a yield of 94%. The mass spectrum of the obtained compound 6 is shown in Figure 2 As shown, it can be seen from the mass spectrum that compound 6 can be synthesized.
[0077] Example 6
[0078] This embodiment is for preparing compound VII, the reaction formula is as follows, and its preparation method includes the following steps.
[0079]
[0080] (1) In a 500 ml three-necked flask, 11.4 g of squaric acid, 9.4 g of lithium tetrafluoroborate, and 84 g of dimethyl carbonate were added and stirred to form a first solution.
[0081] (2) Then, 8.5 g of silicon tetrachloride was slowly added dropwise to carry out substitution reaction at 35° C. for 2.5 h, and then the temperature was raised to 60° C. to carry out reaction for 4.5 h.
[0082] (3) The reaction solution was vacuumed to remove acid, concentrated, crystallized, filtered, and vacuum dried at 120°C to obtain 15.1 g of compound VII with a yield of 90%. The mass spectrum of the obtained compound VII is shown in Figure 3 As shown, it can be seen from the mass spectrum that compound 7 can be synthesized.
[0083] Example 7
[0084] This embodiment is for preparing compound VIII. The reaction formula is as follows. Its preparation method includes the following steps.
[0085]
[0086] (1) In a 500 ml three-necked flask, add 11.4 g of squaric acid and 85 g of tetrahydrofuran and stir to mix uniformly to form a first solution.
[0087] (2) Then, 12.9 g of dimethyldichlorosilane and 11 g of triethylamine were slowly added dropwise, and the temperature was raised to 70° C. to carry out reflux reaction for 24 h.
[0088] (3) The reaction solution was vacuum-evacuated to remove acid, concentrated, crystallized, filtered, and vacuum-dried at 60° C. to obtain 15.5 g of compound 8 with a yield of 91%.
[0089] Part II: Application of Squaric Acid Derivatives in Batteries
[0090] 1.1 Preparation of non-aqueous electrolyte
[0091] In a glove box filled with nitrogen (water content ≤1ppm, oxygen content ≤1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were dehydrated to make the water content of the solution ≤1ppm (5% solution mass activated 4A molecular sieves were added), and then 87g of the mixed solution was prepared in a mass ratio of EC:EMC:DEC=1:1:1 and stirred evenly, and then 12.9g of lithium hexafluorophosphate was slowly added to the mixed solution, stirred evenly to make it completely dissolved, and then 0.1g of compound 1 was added, stirred evenly to make it completely dissolved, to form non-aqueous electrolyte 1#.
[0092] 1.2 Preparation of positive electrode
[0093] Lithium cobalt oxide, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:1.5:3.5 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on aluminum foil for current collector, and then cold-pressed, trimmed, cut into pieces, and stripped to form lithium-ion battery positive electrode sheets that meet the requirements.
[0094] 1.3 Preparation of negative electrode
[0095] Artificial graphite, conductive agent SuperP, thickener CMC and adhesive SBR (styrene-butadiene rubber latex) are made into slurry in a mass ratio of 95:2:1:2, mixed evenly, coated on both sides of copper foil with the mixed slurry, dried and rolled to obtain a negative electrode sheet, thus making a lithium-ion battery negative electrode sheet that meets the requirements.
[0096] 1.4 Preparation of lithium-ion batteries
[0097] The positive electrode sheet, separator and negative electrode sheet are stacked to form a square battery cell, which is packaged with a polymer and then vacuum dried at 60°C for 12 hours. Then, a non-aqueous electrolyte is injected into the battery cell in a glove box, and then it is processed through processes such as formation and capacity division to produce a lithium-ion battery No. 1 with a capacity of 1000mAh.
[0098] The square acid derivative compound in Examples 2 to 7 was substituted for the square acid derivative compound in Example 1 to prepare non-aqueous electrolytes 2# to 16#, and the square acid derivative compound was not added to prepare non-aqueous electrolyte 17#. The compositions of non-aqueous electrolytes 2# to 17# are shown in Table 1. The same positive and negative electrode sheets and lithium ion battery preparation methods as in 1.1 to 1.4 were used to prepare lithium ion batteries 2# to 17#.
[0099] Table 1 Composition of non-aqueous electrolyte 2#~17#
[0100] Group Non-aqueous organic solvent / g Lithium salt / g Additives / g Non-aqueous electrolyte 1# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 1 / 0.1 Non-aqueous electrolyte 2# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 1 / 0.3 Non-aqueous electrolyte 3# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 2 / 0.1 Non-aqueous electrolyte 4# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 2 / 0.3 Non-aqueous electrolyte 5# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 3 / 0.1 Non-aqueous electrolyte 6# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 3 / 0.3 Non-aqueous electrolyte 7# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 4 / 0.1 Non-aqueous electrolyte 8# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 4 / 0.3 Non-aqueous electrolyte 9# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 5 / 0.1 Non-aqueous electrolyte 10# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 5 / 0.3 Non-aqueous electrolyte 11# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 6 / 0.1 Non-aqueous electrolyte 12# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 6 / 0.3 Non-aqueous electrolyte 13# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.7]]> Compound 7 / 0.1 Non-aqueous electrolyte 14# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 / 12.9]]> Compound 7 / 0.3 Non-aqueous electrolyte 15# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 12.7]]> Compound 8 / 0.1 Non-aqueous electrolyte 16# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 12.9]]> Compound 8 / 0.3 Non-aqueous electrolyte 17# EC:EMC:DEC=1:1:1 / 87.0 <![CDATA[LiPF 6 13.0]]> /
[0101] Lithium-ion batteries 2# to 17# were subjected to high-temperature storage performance tests and high-temperature fast-charge cycle performance tests. The test conditions are as follows and the test results are shown in Table 2.
[0102] High temperature storage performance test: At room temperature (25°C) and an upper voltage of 4.53V, the lithium-ion battery is charged and discharged at 0.3C / 0.3C, and the discharge capacity is recorded as C 0 Then, place the battery in a 60℃ oven for 7 days, take it out and wait for the battery temperature to drop to 25℃, then discharge it at 0.3C, and record the discharge capacity as C 1 Then the lithium-ion battery is charged and discharged at 0.3C / 0.3C, and the discharge capacity is recorded as C 2 .
[0103] Capacity retention rate = C 1 / C 0 *100%
[0104] Capacity recovery rate = C 2 / C 0 *100%
[0105] High temperature fast charge cycle performance test: Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge at 2C constant current to a voltage of 4.53V, then charge at 4.53V constant voltage to a current of 0.05C, then discharge at 1C constant current to a voltage of 3.0V, and record the first cycle discharge capacity of the battery as C 0 This is one charge and discharge cycle. Then, 2C / 1C charging and discharging were performed at 45°C for 300 cycles, and the discharge capacity was recorded as C 1 .
[0106] Capacity retention rate = C 1 / C 0 *100%
[0107] Table 2 High temperature storage performance and high temperature fast charge cycle performance test results of lithium ion batteries 2#~17#
[0108]
[0109]
[0110] From the results in Table 2, it can be seen that the high temperature storage performance and high temperature fast charge cycle performance of lithium ion batteries 1#~16# are better than those of lithium ion battery 17#. This is because the square acid derivative compound is used as an additive in lithium ion batteries 1#~16#, and the square acid structure on the left has high stability and conjugated structure, which can be complexed with the positive electrode metal ions to stabilize the structure. On the other hand, the right half structure of the square acid derivative compound can introduce heteroatoms to form bonds such as S=O, C=O, PR, BR, Si-R, etc., which can increase the solubility of the square acid derivative compound in the electrolyte, and at the same time, a stable SEI film can be formed during the battery cycle, which can inhibit the dissolution of metal ions in the positive electrode material and cause the oxidative decomposition of the electrolyte, and can improve the high temperature storage and high temperature cycle performance of the secondary battery at high voltage.
[0111] In addition, through the comparison of lithium-ion batteries 1# to 16#, it can be seen that lithium-ion batteries 1# to 2# and lithium-ion batteries 9# to 10# have better performance. This is because the right structure of compound 1 is a ring structure similar to vinyl sulfate, which combines the dual effects of squaric acid and vinyl sulfate to achieve a synergistic gain effect. The right structure of compound 5 contains more PF bonds. The rupture of the PF bonds in the battery formation stage can make the SEI film formed contain more LiF, making the SEI film formed more stable, thereby greatly improving the high-temperature performance of the battery.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A squaric acid derivative compound, characterized in that: The structural formula is as shown in Formula 1, Formula 2, Formula 3 or Formula 4, X is selected from SO2, SO, CO, BR, PR, PO-R or Si-R2, Y is selected from B-R2, P-R2, PO-R2 or P-R4, Z is selected from SO, C or PR, W is selected from B, P or P-R2, R is hydrogen, halogen or C1-C3 alkyl, 2. The squaric acid derivative compound according to claim 1, characterized in that including at least one of Compound 1 to Compound 8, 3. The method for preparing a squaric acid derivative compound according to any one of claims 1 to 2, characterized in that: Includes steps: (1) mixing a squaric acid and a solvent to form a first solution; (2) adding an electrophilic reagent to the first solution to carry out a substitution reaction, or first adding a salt to the first solution and then adding the electrophilic reagent to carry out a substitution reaction, wherein the electrophilic reagent is a silicon halide, a phosphorus halide, a boron halide, a sulfur halide or an ester compound, and the salt is a lithium salt or a sodium salt; (3) Purification and drying after the reaction.
4. The method for preparing a squaric acid derivative compound according to claim 3, characterized in that: The reaction temperature of the substitution reaction is -20 to 90°C.
5. The method for preparing a squaric acid derivative compound according to claim 3, characterized in that: The molar ratio of the squaric acid to the electrophilic reagent is 1:0.5-2.
1.
6. The method for preparing a squaric acid derivative compound according to claim 3, characterized in that: An oxidation step is included between step (2) and step (3) to oxidize the product of the substitution reaction.
7. The method for preparing a squaric acid derivative compound according to claim 3, characterized in that: The electrophilic reagent is selected from at least one of silicon tetrachloride, trimethylsilyl chloride, dimethylsilyl chloride, monomethylsilyl chloride, thionyl chloride, phosphorus trichloride, phosphorus pentachloride, phosphorus tribromide, phosphorus pentabromide, boron trichloride, boron trifluoride, boron trifluoride ether complex, dimethyl carbonate complex, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and the salt is selected from lithium hexafluorophosphate, lithium tetrafluoroborate, sodium hexafluorophosphate or sodium tetrafluoroborate.
8. Use of the squaric acid derivative compound according to claim 1 or 2, or the squaric acid derivative compound prepared by the method for preparing the squaric acid derivative compound according to any one of claims 3 to 7 in a secondary battery.
9. An electrolyte comprising a non-aqueous organic solvent, an electrolyte salt and an additive, characterized in that: The additive comprises the squaric acid derivative compound according to claim 1 or 2, or the squaric acid derivative compound prepared by the preparation method of squaric acid derivative compound according to any one of claims 3 to 7, and the squaric acid derivative compound accounts for 0.01 to 2.00% of the electrolyte mass.
10. The electrolyte according to claim 9, characterized in that The electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorophosphate and lithium difluorobis(oxalato)phosphate, and the non-aqueous organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, butyl acetate, γ-butyrolactone, propyl propionate, butyl propionate and ethyl butyrate.
Citation Information
Patent Citations
A lithium ion battery electrolyte and a lithium ion battery contain that electrolyte
CN109273764A
Additive, electrolyte containing additive and lithium ion battery
CN113764737A
Nonaqueous electrolyte, and power storage device using the same
JP2015138662A